Antimicrobial effect, frictional resistance, and surface roughness of stainless steel orthodontic brackets coated with nanofilms of silver and titanium oxide: a preliminary study. Issue 6 (9th February 2017) - Ghasemi, Tania; Arash, Valiollah; Rabiee, Sayed Mahmood; Rajabnia, Ramazan; Pourzare, Amirhosein; Rakhshan, Vahid
Abstract: Nano‐silver and nano‐titanium oxide films can be coated over brackets in order to reduce bacterial aggregation and friction. However, their antimicrobial efficacy, surface roughness, and frictional resistance are not assessed before. Fifty‐five stainless‐steel brackets were divided into 5 groups of 11 brackets each: uncoated brackets, brackets coated with 60 µm silver, 100 µm silver, 60 µm titanium, and 100 µm titanium. Coating was performed using physical vapor deposition method. For friction test, three brackets from each group were randomly selected and tested. For scanning electron microscopy and atomic‐force microscopy assessments, one and one brackets were selected from each group. For antibacterial assessment, six brackets were selected from each group. Of them, three were immediately subjected to direct contact with S. mutans . Colonies were counted 3, 6, 24, and 48 h of contact. The other three were stored in water for 3 months. Then were subjected to a similar direct contact test. Results pertaining to both subgroups were combined. Groups were compared statistically. Mean (SD) friction values of the groups 'control, silver‐60, silver‐100, titanium‐60, and titanium‐100' were 0.55 ± 0.14, 0.77 ± 0.08, 0.82 ± 0.11, 1.52 ± 0.24, and 1.57 ± 0.41 N, respectively ( p  =   .0004, Kruskal–Wallis). Titanium frictions were significantly greater than control ( p  <   .05), but silver groups were not ( p  >   .05, Dunn). In the uncoated group, colony count increased exponentially within 48 h. The coated groups showed significant reductions in colony count ( p  <   .05, two‐way‐repeated‐measures ANOVA). In conclusions, all four explained coatings reduce surface roughness and bacterial growth. Nano‐titanium films are not suitable for friction reduction. Nano‐silver results were not conclusive and need future larger studies. Abstract : Both 60‐ and 100‐µm films of silver and titanium oxide can efficiently reduce bacterial count after 3 h. They also reduce surface roughness. Both of these ions can be coated over the surface of brackets for bacterial reduction purposes, as long as the slots are not coated.